1985
DOI: 10.1136/jcp.38.1.12
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody that detects HLA-D region antigen in routinely fixed, wax embedded sections of normal and neoplastic lymphoid tissues.

Abstract: SUMMARY We describe the use of a monoclonal antibody (TAL-IB5) to HLA-D region a-chains that reacts well with HLA-D positive cells in normal and neoplastic lymphoid tissues fixed in routine fixatives and embedded in paraffin wax in the conventional fashion. This antibody should prove to be useful in routine histological investigations of lymphoid and possibly other neoplasms as well as other non-neoplastic conditions where the immune system plays an important part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…26,27 In addition to reagents defining MHC class I glycoproteins, panel antibodies included the monomorphic MHC class II HLA-DR marker TAL IB5. 28 Differentiation markers included TMH1 defining the melanocytic 75 kD tyrosinase-related protein TRP1 [29][30][31] and Dako T6 (CD1a). 32 Immunocytochemistry was performed on 5 m cryostat sections using a streptavidin-peroxidase technique.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 In addition to reagents defining MHC class I glycoproteins, panel antibodies included the monomorphic MHC class II HLA-DR marker TAL IB5. 28 Differentiation markers included TMH1 defining the melanocytic 75 kD tyrosinase-related protein TRP1 [29][30][31] and Dako T6 (CD1a). 32 Immunocytochemistry was performed on 5 m cryostat sections using a streptavidin-peroxidase technique.…”
Section: Methodsmentioning
confidence: 99%
“…The primary dilutions were 1:20, 1:5000, 1:5000 and 1:10000 respectively. In addition to the hormonal antibodies, we used two antibodies against the non-polymorphous region of the HLA-DR antigen, EPl13 (gift of Dr. H. G. Thiele, Hamburg, FRG [16[) and TAL-B 5 (gift of C. Dixon, London, UK [17]) known to react on paraffin embedded tissue at dilutions of I : 10 000 and 1 : 20 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The murine monoclonal antibody TAL-1 B5 to a monomorphic determinant of the HLA-DR a-chain (weakly cross-reacting with the fl-chain) originally raised by Adams et al (1983) and shown to react with fixed and paraffinembedded tissues (Epenetos et al, 1985) Immunoperoxidase staining The indirect immunoperoxidase technique used in this study was performed as previously described (Bartek et al, 1985a) using peroxidase conjugated rabbit anti-mouse immunoglobulin antiserum (Dako, Copenhagen, Denmark) as the second antibody, diaminobenzidine (Sigma, Deisenhofen, FRG) as chromogen and haematoxylin to counterstain nuclei.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%